International Legal Regulation of Activities for the Safe Use of Outer Space - M. Ishkibayeva, Gulmira; Nurmukhankyzy, Daniya (Law, State and Telecommunications Review, 2022)
[Purpose] It is impossible to imagine the life of a modern person without space technologies. International crews of astronauts have been working in orbit as part of the International Space Station for the past fifteen years. The purpose of the study is to assess the problems of legal regulation of activities related to the use of space communications. [Methodology] According to the specifics of the subject and the purpose of the research, we applied dialectical, historical, comparative and system-structural methods. [Findings] The international legal instruments of general statutory load on outer space subjects and specialised regulation with a focus on individual aspects of the safety of space activities were studied. To clarify the scope of relevant objects of outer space, the causes of emerging dangers as a result of space activities were identified. The development of a set of regulations for the commercial use of space communications was demonstrated. [Practical Implications] The practical significance of the study is determined by the fact that the safety of space activities in recent years has become one of the most serious problems of space activities.